Studi Mediasi Sekuensial: Mitigasi Turnover Intention Pada Tenaga Kerja Subsektor Arsitektur Di Era Transformasi Digital - Soraya, Altheannisa Agatha; Ardiyanti, Niken (UI Scholars Hub, 2024)
This study aims to analyze the role of resilience, job security, social support, and job satisfaction on turnover intention among 300 workers in the architecture sector in Indonesia. Using Covariance Based Structural Equation Model, this study found that social support and job satisfaction act as mediators in the relationship between resilience and turnover intention. Social support has a positive influence on turnover intention, different from earlier findings, which may be due to the context of the Indonesian architecture sector. This study contributes to the literature by testing the sequential mediating relationships between resilience, social support, job satisfaction, and turnover intention. Practical implications suggest that this model can be tested in other industries with diverse cultures and characteristics, as well as further studying the potential relationship between job security and perceived social support in more dynamic jobs and diverse levels of job security.